Perbedaan Angka Keberhasilan Pemasangan Laryngeal Mask Airway Antara Teknik Cuff Dikempiskan dan Dikembangkan Sebagian pada Pasien Dewasa - Isbhat Nawakhil; Raden Sugeng Riyadi; Anita Setyowati (Lembaga Pengembangan Kinerja Dosen, 2025)
Laryngeal Mask Airway (LMA) insertion is an important part of airway management during general anesthesia. Two commonly used techniques are deflated cuff and partially inflated cuff. Choosing the right technique can increase the success rate of insertion and reduce complications such as air leaks or tissue trauma. This study aims to determine the difference in the success rate of laryngeal mask airway inserstion between deflated and partially inflated cuff techniques in adult patients at PKU Muhammadiyah Gamping Hospital. This study employed a quantitative method with a quasi-experimental design with a two group posttest only design. The sample consisted of 40 patients; and divided into two groups. Data were analyzed using the Mann-Whitney test. The results showed that the partially inflated cuff technique had a higher success rate (75%) than the deflated cuff technique (25%). The statistical test showed a significant difference with a p value <0,05. There was a significant difference in the success of LMA insertion between the two techniques. The partially inflated cuff technique is more recommended to increase the effectiveness and safety of the procedure.